Observation of a new Ξ0b state - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2021)
Using a proton-proton collision data sample collected by the LHCb experiment, corresponding to an integrated luminosity of 8.5 fb−1, the observation of a new excited Ξ0b resonance decaying to the Ξ−bπ+ final state is presented. The state, referred to as Ξb(6227)0, has a measured mass and natural width of m(Ξb(6227)0)=6227.1+1.4−1.5±0.5 MeV and Γ(Ξb(6227)0)=18.6+5.0−4.1±1.4 MeV, where the uncertainties are statistical and systematic. The production rate of the Ξb(6227)0 state relative to that of the Ξ−b baryon in the kinematic region 2<η<5 and pT<30 GeV is measured to be fΞb(6227)0fΞ−bB(Ξb(6227)0→Ξ−bπ+)=0.045±0.008±0.004, where B(Ξb(6227)0→Ξ−bπ+) is the branching fraction of the decay, and fΞb(6227)0 and fΞ−b represent fragmentation fractions. Improved measurements of the mass and natural width of the previously observed Ξb(6227)− state, along with the mass of the Ξ−b baryon, are also reported. Both measurements are significantly more precise than, and consistent with, previously reported values.
Im Titel ist "0" hochgestellt und "b" in Ξ0b tiefgestellt
Gesehen am 11.03.2021